Renal primary cilia lengthen in the progression of diabetic kidney disease - Bai, Yunfeng; Li, Ping; Liu, Jiaona; Zhang, Lu; Cui, Shaoyuan; Wei, Cuiting; Fu, Bo; Sun, Xuefeng; Cai, Guangyan; Hong, Quan; Chen, Xiangmei (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease, and its early pathogenesis is critical. Shear stress caused by glomerular hyperfiltration contributes to the initiation of kidney injury in diabetes. The primary cilium of renal tubular epithelial cells (RTECs) is an important mechanical force sensor of shear stress and regulates energy metabolism homeostasis in RTECs to ensure energy supply for reabsorption functions, but little is known about the alterations in renal cilium number and length during the progression of DKD. Here, we demonstrate that aberrant ciliogenesis and dramatic increase in cilium length, the number of ciliated cells and the length of cilia are positively correlated with diabetic kidney disease class in the kidney biopsies of DKD patients. This finding was further confirmed in STZ-induced or db/db diabetic mice. These findings suggest that the number and length of renal cilia may be clinically relevant indicators and that cilia will be attractive therapeutic targets for DKD.